Efficient stabilizing agent-free synthesis of gold nanoparticles via square-wave pulse deposition for enhanced catalytic performance in ethanol electrooxidation - Setia Budi; Aulia Siti Pathoni; Annisa Auliya; Suci Winarsih; Mohammad Hamzah Fauzi; Yusmaniar; Babay Asih Suliasih; Hilman Syafei (Materials Reports: Energy)
The pressing environmental concerns and the depletion of fossil fuel reserves necessitate a transition toward sustainable energy sources. Ethanol, a renewable biomass-derived fuel, is a promising alternative due to its availability and high energy density. This study investigates the synthesis of gold nanoparticles (Au NPs) via a square-wave pulse deposition technique, aiming to enhance catalytic activity for ethanol electrooxidation. By varying pulse durations, we were able to exert precise control over Au NP size and distribution without stabilizing agents. Characterization using field emission scanning electron microscopy and X-ray diffraction techniques confirmed the formation of clustered nanoparticles of metallic gold phase. Electrochemical characteristics analyses revealed that Au NPs synthesized with a 900 ms pulse duration exhibited the lowest charge transfer resistance and the highest electrochemically active surface area. The electrocatalytic performance test of these Au NPs demonstrated an anodic current density of 2.5 mA cm−2 and a Tafel slope of 78 mV dec−1, indicating superior catalytic performance and reaction kinetics. Additionally, the Au NPs showed high resistance to poisoning, as evidenced by a low jb/jf ratio of 0.28 and stable chronoamperometric response. These findings underscore the potential of this synthesis method for producing high-performance electrocatalysts utilized in exploiting ethanol's potential as an environmentally friendly energy carrier.